The Impact of Variations in Fasting Duration on Hemodynamic Status and Blood Sugar Levels in Electional Surgery Patients - Irwadi Irwadi; Fatimah Fatimah; Yenni Elfira (Indonesian Journal of Global Health Research, 2026)
Preoperative fasting is a standard applied in surgical services to prevent aspiration, but in hospital practice, fasting often occurs that exceeds the recommendations of the American Society of Anesthesiologists (ASA) which recommends a minimum fast of 6-8 hours, the negative impact of extended fasting will affect the hemodynamic and metabolic status of patients. This study aims to analyze the impact of variations in fasting duration with hemodynamic status and blood sugar levels in patients. This study used a quantitative design with a cross-sectional approach with a sample of 252 elective surgical patients collected by purposive sampling. Data collected included demographic characteristics, ASA physical status I-II, fasting duration, and preoperative clinical parameters. with inclusion criteria: respondents aged 18-55 years, ASA physical status I-II, undergoing elective surgery while exclusion criteria were patients with metabolic disorders such as diabetes mellitus or unstable cardiovascular disorders and cytotoxic patients. Data were collected using observation sheets related to demographics, physical status, type of surgery, last meal, and post-operative complaints, as well as a Non-Invasive Blood Pressure Monitor (NIBP) to measure hemodynamics, a pulse oximeter for oxygen saturation, and a glucometer for glucose levels. The results of the one way anova test showed that variations in fasting duration did not affect hemodynamics (p > 0.05), but did affect blood sugar levels where the value (p < 0.05). It was found that these findings confirm that pre-operative fasting beyond the recommendation can affect the patient's metabolic status, so that fasting duration management according to ASA standards is important to maintain the patient's metabolic and physiological stability.